Answer: 390 miles
Step-by-step explanation:
Answer:
f(x)= 6x+9....
Step-by-step explanation:
The given equation is:
y-6x-9=0
Add 6x+9 at both sides:
y-6x-9+6x+9=0+6x+9
Solve the like terms:
on the L.H.S -6x will be cancelled out by +6x and -9 will be cancelled out by +9
y=6x+9
Now convert it in function notation:
f(x)=y
f(x)= 6x+9....
Answer:
108 - 84i
Step-by-step explanation:
12( 9-7i)
Distribute
12*9 - 12*7i
108 - 84i
Answer:
34.8
Step-by-step explanation:
36-1.2 = 34.8
-1/4*x^2-x+3=-1/4*(x^2+4x)+3=-1/4*(x^2+4x+4)+4=-1/4*(x+2)^2+4
x0=-2